Potent inhibitors of human LAT1 (SLC7A5) transporter based on dithiazole and dithiazine compounds for development of anticancer drugs - Napolitano, Lara; Scalise, Mariafrancesca; Koyioni, Maria; Koutentis, Panayiotis; Catto, Marco; Eberini, Ivano; Parravicini, Chiara; Palazzolo, Luca; Pisani, Leonardo; Galluccio, Michele; Console, Lara; Carotti, Angelo; et al. (Biochemical pharmacology, 2017)
[Display omitted] The LAT1 transporter is acknowledged as a pharmacological target of tumours since it is strongly overexpressed in many human cancers. The purpose of this work was to find novel compounds exhibiting potent and prolonged inhibition of the transporter. To this aim, compounds based on dithiazole and dithiazine scaffold have been screened in the proteoliposome experimental model. Inhibition was tested on the antiport catalysed by hLAT1 as transport of extraliposomal [3H]histidine in exchange with intraliposomal histidine. Out of 59 compounds tested, 8 compounds, showing an inhibition higher than 90% at 100µM concentration, were subjected to dose-response analysis. Two of them exhibited IC50 lower than 1µM. Inhibition kinetics, performed on the two best inhibitors, indicated a mixed type of inhibition with respect to the substrate. Furthermore, inhibition of the transporter was still present after removal of the compounds from the reaction mixture, but was reversed on addition of dithioerythritol, a S-S reducing agent, indicating the formation of disulfide(s) between the compounds and the protein. Molecular docking of the two best inhibitors on the hLAT1 homology structural model, highlighted interaction with the substrate binding site and formation of a covalent bond with the residue C407. Indeed, the inhibition was impaired in the hLAT1 mutant C407A confirming the involvement of that Cys residue. Treatment of SiHa cells expressing hLAT1 at relatively high level, with the two most potent inhibitors led to cell death which was not observed after treatment with a compound exhibiting very poor inhibitory effect.